Effect of Simvastatin on Polycystic Ovarian Syndrome (PCOS) - Asma Mumtaz, Shazia Rafiq, Hira Irum, Fozia Khanam, Kausar Fatima, Javeria Mumtaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the effect of simvastatin on biochemical parameters in women with polycystic ovarian syndrome (PCOS). Study Design: A prospective cohort study. Place and Duration of the Study: The Department of Gynecology and Obstetrics, Ibn-e-Sina Hospital Multan, Pakistan from March 2021 to August 2021. Material and Methods: The study was performed at the Department of Gynecology and Obstetrics, a tertiary care center affiliated with Ibn-e-Siena Hospital & Research Institute Multan, Pakistan. We screened 236 patients with PCOS ranging in age 20-40 years between March and August 2021.. Patients with hypothyroidism, congenital adrenal hyperplasia (CAH), Cushing syndrome (CS), ovarian tumors and on simvastatin therapy were excluded and those who were not willing to take part in this study were also excluded. All patients were given simvastatin 20 mg per day orally for 3 months. Venous blood samples were drawn before and after therapy and sent to the laboratory of the hospital for total cholesterol, total testosterone and low density lipoprotein (LDL-C) level. These tests were done before and after intervention with simvastatin treatment. Results: Age range in this study was from 20 to 40 years with mean age of 29.41±4.44 years, mean duration of disease was 13.78±3.60 months, mean body mass index (BMI) 26.42±2.00 Kg/m2 , mean Total Cholesterol 185.37±19.11 mg/dl, mean Total Testosterone 2.41±1.39 pmol/ L and mean LDL-C was 95.94±5.63 mg/dl. The majority of patients were from 20-30 years age group (68.6%). Decreased cholesterol was seen in 16.5% patients, decreased testosterone in 18.6% patients and decreased LDL-C in 28.8% patients. Conclusion: The treatment of PCOS with simvastatin was found to be beneficial in improving several key features of PCOS including reduction in in total cholesterol, testosterone, and LDL-C levels. Keywords: Polycystic ovarian syndrome, simvastatin, testosterone